2020
DOI: 10.1186/s13014-020-01497-4
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant radiotherapy improves overall survival for T3/4N+M0 rectal cancer patients: a population-based study of 20300 patients

Abstract: Background: Neoadjuvant radiotherapy (RT) has been shown to improve local control; however, whether it can improve overall survival (OS) in locally advanced rectal cancer (LARC) patients remains controversial. We therefore aimed to examine the benefits of surgery alone, neoadjuvant radiotherapy (RT), adjuvant RT, and surgery plus chemotherapy in stage II (T3/4N0M0) and III (any T and N + M0) on the OS of rectal cancer patients. Methods: Date from the Surveillance, Epidemiology, and End Results (SEER) database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
1
18
0
1
Order By: Relevance
“…The utilisation of neoadjuvant radiotherapy (7.8%) and neoadjuvant chemotherapy (5.9%) in older adults in our study was low, however, similar to other studies [17] [19]. The role of neoadjuvant radiotherapy and CRT in rectal can- [27]. Other reasons for the low utilisation rates include patient preferences for no neoadjuvant and/or adjuvant therapy, and patient and clinician concerns about excess toxicity such as faecal incontinence and sexual dysfunction, which are more pronounced in older patients [28] [29] [30].…”
Section: Discussionsupporting
confidence: 86%
“…The utilisation of neoadjuvant radiotherapy (7.8%) and neoadjuvant chemotherapy (5.9%) in older adults in our study was low, however, similar to other studies [17] [19]. The role of neoadjuvant radiotherapy and CRT in rectal can- [27]. Other reasons for the low utilisation rates include patient preferences for no neoadjuvant and/or adjuvant therapy, and patient and clinician concerns about excess toxicity such as faecal incontinence and sexual dysfunction, which are more pronounced in older patients [28] [29] [30].…”
Section: Discussionsupporting
confidence: 86%
“… 3 , 4 This combined modality approach decreases recurrence rates and improves survival compared with surgery only. 4 , 5 The most frequently used neoadjuvant treatment strategy for LARC is a combination of radiotherapy (25 × 2 Gy or 28 × 1.8 Gy) and fluoropyrimidine-based chemotherapy [e.g., capecitabine or 5-fluorouracil (5FU)]. Hereby 15–20% of LARC patients achieve a pathological complete response (pCR) in which no tumor is found in the surgical resection specimen.…”
mentioning
confidence: 99%
“…14 A 2020 Chinese-based study showed that the majority of patients (53.6%) infected by SARS-CoV-2 were aged 50 or older, which coincides with the predilection age of colorectal cancer, that is, colorectal cancer patients might be at higher risk of acquiring COVID-19 given their average age. 16,17 While hospitals worldwide attempt to isolate COVID-19 patients to specialized hospital wards, many cases are under-recognized or received delayed diagnoses exposing patients in the general medicine ward. 18 CRC is the third most common tumor in men and the second in women.…”
Section: Colon Cancer Managementmentioning
confidence: 99%